Autonomous DC-link voltage restoration for grid-connected power converters providing virtual inertia - Guo, Ke (2020)
Renewable energy sources have been increasingly adopted to reduce greenhouse emissions. However, they are normally interfaced with power grids through grid-connected power converters without any inertia contribution. This will lead to the decreased power system inertia. As a solution, the method of inertia emulation by power converters has been reported to handle this problem. However, the DC-link capacitors of power converters cannot restore their voltages after injecting the power required by inertia emulation. Thus, if the load change causes another DC-link voltage drop, the undesirable overmodulation may appear. Moreover, power converters cannot provide multiple inertia support during cascading frequency events without the DC-link voltage recovery. To address the above concerns, this paper proposes an autonomous DC-link voltage restoration method that allows the restoration of DC-link voltages after individual frequency events. Simulation and experimental results verify the feasibility of the proposed method.